A bottom-up approach for a private fisheries extension system: A framework and action plan for an aqua-chamber of commerce in India - Ojha, Shekhar Nath; Dey, Suman; Babu, Suresh Chandra (International Food Policy Research Institute, 2020)
Aquaculture and fisheries continues to be a sector that has not received adequate attention for its contribution to food security goals across the globe. This sector is predicted to grow at a fast rate in the next 40 years. In the Indian context, the government has prioritized the aquaculture and fisheries sector by establishing an independent federal ministry. However, the public extension system in India still lacks resources and strategies to address the needs of fish farmers and fishers. This has created a space for the private extension system to play a pivotal role in providing appropriate skills and training to farmers and fishers. Considering the present challenges in the aquaculture and fisheries sector, this paper proposes the creation of an Aqua-Chamber of Commerce (ACC) as a viable bottom-up approach to improve the performance of the sector by providing adequate support to private extension system. Additionaly, the ACC will also help in improving the public extension system, facilitating the business ecosystem and strategies, and advocating for major policy reforms in the sector.